Neoliberalism, austerity and social work with children and families: challenges and critical/radical possibilities. (1st November 2021) - Rogowski, Steve
Abstract : In the UK, neoliberalism and associated austerity have dominated social work and welfare provision over the last decade. Consequences include severe financial cuts to social work with children and families, as well as public services generally, and large increases in poverty and inequality. Despite increasing numbers of people in difficulty, the social work and welfare system has become more punitive and presents ongoing threats to social work's commitment to human rights and social justice. This article examines such developments and includes the views of practitioners. Despite the strength and depth of challenges, it argues that critical/radical possibilities remain for practitioners to work both individually with service users and collectively. Such opportunities need to be taken with a view to working towards a more just and equal society, this being a much-needed antidote to the unequal neoliberal world we currently inhabit.